1983
DOI: 10.1016/0014-5793(83)80240-3
|View full text |Cite
|
Sign up to set email alerts
|

Fluorescence associated with the type 3 copper center of laccase

Abstract: Laccases isolated from the lacquer tree Rhus vernicifera and the fungus Polyporus versicolor show fluorescence emission near 420 run and phosphorescence emission in the 440-465 mn region. The fluorescence and phosphorescence excitation spectra for both laccases show maxima in the 315-330 mn range, a spectral region corresponding to the absorbance maxima for the type 3 binuclear Cu centers of the two enzymes. Additional evidence is presented for the association of the newly discovered emissions with the type 3 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 14 publications
1
8
0
Order By: Relevance
“…X-ray absorption edge measurements on T2Dr and T2D0X lacease preparations have conclusively shown that these contain Cu(I)-Cu(I) and Cu(II)-Cu(II) type 3 centers, respectively (LuBien et al, 1981). Comparisons of the fluorescence and phosphorescence spectra of native and T2D0X laceases recently performed in our laboratories (Wynn et al, 1983b) further support this conclusion. Protein denaturation did not accompany type 2 copper removal in the present study, as the optical, EPR, and ferrocyanide turnover characteristics of native lacease were restored through the addition of Cu(II) to the T2D derivative.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…X-ray absorption edge measurements on T2Dr and T2D0X lacease preparations have conclusively shown that these contain Cu(I)-Cu(I) and Cu(II)-Cu(II) type 3 centers, respectively (LuBien et al, 1981). Comparisons of the fluorescence and phosphorescence spectra of native and T2D0X laceases recently performed in our laboratories (Wynn et al, 1983b) further support this conclusion. Protein denaturation did not accompany type 2 copper removal in the present study, as the optical, EPR, and ferrocyanide turnover characteristics of native lacease were restored through the addition of Cu(II) to the T2D derivative.…”
Section: Discussionsupporting
confidence: 60%
“…or inhibition experiments with anions (i.e., N3', SCN", F', and CN') known to ligate this site (Holwerda et al, 1982). The availability of tree lacease specifically depleted of the type 2 copper atom (T2D) (Graziani et al, 1976) has inspired numerous new approaches to understanding the behavior of the type 2 and 3 centers (Lubien et al, 1981;Spira et al, 1982;Winkler et al, 1982;Morpurgo et al, 1980a,b;Avigliano et al, 1981;Farver et al, 1982;Wynn et al, 1983b;Reinhammar, 1981Reinhammar, , 1983. Nevertheless, only a single rate study of T2D lacease redox reactions has appeared (Reinhammar & Oda, 1979).…”
mentioning
confidence: 99%
“…The blue, yellow and ABTS-laccase forms are found to show different emission fluorescence spectra when the samples are excited at 330 nm (Fig 4). The emission spectra are centered on 415 nm, 435 nm and 440 nm respectively, and are well known to be due to the type 3 copper binuclear center [33,37]. Noting that the ABTS-adduct emission spectrum is somewhat similar to that of the yellow form, the difference between these forms might be due to the conformational change caused by the covalent attachment of the product which is gating the water channel from the trinuclear site (vide infra).…”
Section: Enzymatic Activitymentioning
confidence: 99%
“…The bi-nuclear T3 copper is diamagnetic. It has an absorbance shoulder in the region of 330 nm and a characteristic fluorescence spectrum [112,113].…”
Section: Laccasementioning
confidence: 99%